Effectiveness of Acceptance and Commitment Therapy on Mental Pain and Life Engagement in Patients with Psoriasis - Shahin Shahidi; Ramezan Hasanzadeh; Bahram Mirzaian (Mazandaran University of Medical Sciences, 2022)
Introduction and purpose: The impact of psoriasis is very high on the quality of patients' life even when a very small area of the body is involved. Psoriasis patients have a lower quality of life than the general population. This study aimed to compare the effectiveness of acceptance and commitment therapy (ACT) on mental pain and life engagement in patients with psoriasis. Methods: This study was a semi-experimental type with a pretest-posttest design and a one-month follow-up with the control group. The statistical population consisted of all patients referred to skin and hair clinics in Boroujerd, Iran, in 2021, who received a definite diagnosis of psoriasis. Among these, 54 patients whose depression rate was higher than the cut-off point were selected through non-random sampling and were replaced in an experimental group (receiving ACT) and a simple random control group (18 in each group). Afterward, eight 90-min sessions of ACT were performed in the experimental group. Data were collected using mental pain (OMMP; Orbach et al., 2003) and life engagement (Hasanzadeh, 2014) questionnaires, as well as the Beck depression inventory (Beck, 1996). Data were analyzed using the SPSS software (version 22) and through repeated measures analysis of variance (ANOVA) test. Results: The results showed that ACT was effective on mental pain (P<0.01, F=31.53) and life engagement (P<0.01, F= 54.08) of patients with psoriasis, which continued until the follow-up stage. Conclusion: It can be concluded that ACT was effective in reducing mental pain and increasing life engagement in patients with psoriasis. It is suggested to use this treatment to reduce the psychological problems of patients with psoriasis.